2017
DOI: 10.1182/blood-2017-04-778225
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in hematologic malignancies

Abstract: Racial and ethnic disparities in patients with solid malignancies have been well documented. Less is known about these disparities in patients with hematologic malignancies. With the advent of novel chemotherapeutics and targeted molecular, cellular, and immunologic therapies, it is important to identify differences in care that may lead to disparate outcomes. This review provides a critical appraisal of the empirical research on racial and ethnic disparities in incidence, survival, and outcomes in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
125
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(133 citation statements)
references
References 48 publications
5
125
0
3
Order By: Relevance
“…In an analysis of more than 37,000 MM patients, Hispanic patients had a significantly worse median overall survival compared with non‐Hispanic white patients (NHWs; 2.4 vs. 2.6 years; p < .006). Asian patients and NHBs did not have significantly different median overall survivals compared with NHWs . In addition to variation in incidence and mortality by race and ethnicity, MM is predominantly a disease of elderly patients, with an average age of diagnosis of 69 years .…”
Section: Introductionmentioning
confidence: 83%
“…In an analysis of more than 37,000 MM patients, Hispanic patients had a significantly worse median overall survival compared with non‐Hispanic white patients (NHWs; 2.4 vs. 2.6 years; p < .006). Asian patients and NHBs did not have significantly different median overall survivals compared with NHWs . In addition to variation in incidence and mortality by race and ethnicity, MM is predominantly a disease of elderly patients, with an average age of diagnosis of 69 years .…”
Section: Introductionmentioning
confidence: 83%
“…In this issue of Blood, Choi et al demonstrated an oncogenic role of RUNX1 in T-cell acute lymphoblastic leukemia (T-ALL), 1 which is in marked contrast to its tumor-suppressive role identified earlier in T-ALL, acute myeloid leukemia (AML), and myelodysplastic syndrome (MDS). R UNX1 is one of the best-characterized hematopoietic transcription factors.…”
mentioning
confidence: 83%
“…1 The authors tested their hypothesis by generating a T-ALL mouse model in which the Runx1 gene was conditionally deleted. They first isolated leukemic cells from the Tal1/Lmo2 doubletransgenic mice and transplanted them into recipient mice, followed by tamoxifen treatment to delete Runx1.…”
mentioning
confidence: 99%
“…The prognostic impact of race in OS is controversial. Racial disparities in outcomes may be related with biologic factors, individual factors, health behaviors, and structural barriers [60]. In a large study from the Surveillance, Epidemiology, and End Results (SEER), with more than 40,000 patients, the differences in OS between patients in the white and black race did not reach statistically significant differences [61].…”
Section: Racementioning
confidence: 99%